The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/02650487.2016.1196030
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking evidence that happy faces impair verbal message comprehension: the case of health warnings in direct-to-consumer pharmaceutical television commercials

Abstract: Risk warning or disclosure information in advertising is only effective in correcting consumers’ judgments if enough cognitive capacity is available to process that information. Hence, comprehension of verbal warnings in TV commercials may suffer if accompanied by positive visual elements. This research addresses this concern about cross-modality interference in the context of direct-to-consumer (DTC) pharmaceutical commercials in the United States by experimentally testing whether positive facial expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…However, these researchers also found that the presence of distraction did not reduce overall consumer perceptions of risk. In a second eye-tracking study of DTCA, Russell et al (2017) reported that message comprehension was impaired by an increased frequency of positive facial expressions during the major statement.…”
Section: Research On Distraction In Dtcamentioning
confidence: 99%
See 1 more Smart Citation
“…However, these researchers also found that the presence of distraction did not reduce overall consumer perceptions of risk. In a second eye-tracking study of DTCA, Russell et al (2017) reported that message comprehension was impaired by an increased frequency of positive facial expressions during the major statement.…”
Section: Research On Distraction In Dtcamentioning
confidence: 99%
“…Of concern is the possibility that the positive affect arising from visual imagery may reduce risk perceptions (Finucane et al 2000; Slovic et al 2007). Prior research using small samples of DTCA found that the presence of positive imagery during the major statement can also inhibit message comprehension (Russell et al 2017). Pairing incongruent audio and visual information has been characterized as a form of distraction (Penney 1989).…”
Section: Research Questionsmentioning
confidence: 99%
“…Next, a recognition memory test was adapted, as utilized in a study of verbal message comprehension in DTC prescription drug commercials (Russell et al ) as well as a study on the impact of efficacy information on the recollection of benefits and risks for a DTC cholesterol drug commercial (O'Donoghue et al ). In this task, participants are presented with a list of 20 risks (or benefits, depending on the condition to which they were exposed) from the original list created by the focus group, and asked to select the four items they heard within the viewed clip.…”
Section: Methodsmentioning
confidence: 99%
“…Consumer advocates worry that as health literacy decreases, consumers will become more reliant on other cognitive heuristics, such as animation, resulting in less well‐informed health‐related decision making and suboptimal medical outcomes. For example, in a study of health warnings within DTC prescription drug advertisements, eye‐tracking data suggest interference between positive visual elements and risk warning comprehension (Russell et al ). In 2016, the FDA announced its interest in better understanding the impact of visual effects such as superimposed text and animated characters on consumer perception of drug advertisements, noting concern that animation “may interfere with message communication” (McCaffry ).…”
mentioning
confidence: 99%
“…That has grabbed immense attention from both academia and industrial field, and collaboration between marketers, neuroscientists, and psychologists in order to better understand what drives consumer behavior and neural processing of advertising in the human brain [60]. For example, it has divided neuroimaging tools that provide evidence on neural correlates of advertising and consumers' behavior into two categories, as follows: (1) recording electrical activity signals such as electroencephalography (EEG) and magnetoencephalography (MEG), and (2) recording metabolic activity signals such as functional magnetic resonance imaging (fMRI) and functional near-infrared spectroscopy (fNIRS) [13,[61][62][63][64][65].…”
Section: An Overview Of Neuroimaging Tools Used In Advertising Researchmentioning
confidence: 99%